The Effect of CEO Tenure, Capital Intensity, and Firm Size On Tax Avoidance - Evi Khusnita Ulfa; Eny Suprapti; Sri Wahjuni Latifah (Universitas Muhammadiyah Malang, 2021)
The aim of this study is to examine the effect of CEO tenure, capital intensity, and firm size on tax avoidance. The sample of this study is 88 companies listed in Indonesia Stock Exchange (IDX) in 2019 were selected through purpose sampling. The data analysis technique used in this study is multiple linear regression analysis. The results of the analysis show that CEO tenure has a positive effect on tax avoidance. This means that the longer the CEO tenure will lead to an increase in tax avoidance. Capital intensity and firm size have no effect on tax avoidance. This research has a novelty in the form impact of CEO tenure, capital intensity, and firm size on tax avoidance. Furthermore, the practical contribution to the government, especially the Directorate General of Taxes, is that long tenure of CEO can lead to tax avoidance. The limitation in this study is the number of samples is less representative in representing the population. This is because there are still companies listed on the IDX that not provide information according to the sample criteria.